Adrenomedullin Deficiency and Aging Exacerbate Ischemic White Matter Injury after Prolonged Cerebral Hypoperfusion in Mice. (16th June 2014) - Mitome-Mishima, Yumiko; Miyamoto, Nobukazu; Tanaka, Ryota; Shimosawa, Tatsuo; Oishi, Hidenori; Arai, Hajime; Hattori, Nobutaka; Urabe, Takao
Abstract : Adrenomedullin was originally isolated from pheochromocytoma cells and reduces insulin resistance by decreasing oxidative stress. White matter lesions induced by aging and hyperglycemia play a crucial role in cognitive impairment in poststroke patients. Here, we examine whether adrenomedullin deficiency and aging exacerbate ischemic white matter injury after prolonged cerebral hypoperfusion. Adrenomedullin heterozygous, wild-type young/aged mice were subjected to prolonged hypoperfusion. Prolonged cerebral hypoperfusion followed by immunohistochemical analysis was used to evaluate white matter injury. After prolonged hypoperfusion, white matter damage progressed in a time-dependent manner in AM +/− group compared with the wild-type group. The number of oligodendrocyte progenitor cells gradually increased after prolonged hypoperfusion, whereas oligodendrocytes decreased following a transient increase, but the ratio of increase was mild in the AM +/− group ( P < 0.05 ) . Oxidative stress was detected in oligodendrocytes, with a larger increase in the AM +/− group ( P < 0.05 ) . Aged mice showed the same tendency, but white matter damage was worse, especially in the aged AM +/− group. Our results demonstrated that white matter injury was increased in adrenomedullin deficiency, which induced oxidative stress. White matter injury was more exacerbated because of hyperglycemia in aged AM +/− group. Adrenomedullin may be an important target in the control of ischemic white matter injury.